Loss of KDM1A in GIP-dependent primary bilateral macronodular adrenal hyperplasia with Cushing's syndrome: a multicentre, retrospective, cohort study. Issue 12 (December 2021) - Chasseloup, Fanny; Bourdeau, Isabelle; Tabarin, Antoine; Regazzo, Daniela; Dumontet, Charles; Ladurelle, Nataly; Tosca, Lucie; Amazit, Larbi; Proust, Alexis; Scharfmann, Raphael; Mignot, Tiphaine; Fiore, Frédéric; et al.
Summary: Background: GIP-dependent primary bilateral macronodular adrenal hyperplasia with Cushing's syndrome is caused by aberrant expression of the GIP receptor in adrenal lesions. The bilateral nature of this disease suggests germline genetic predisposition. We aimed to identify the genetic driver event responsible for GIP-dependent primary bilateral macronodular adrenal hyperplasia with Cushing's syndrome. Methods: We conducted a multicentre, retrospective, cohort study at endocrine hospitals and university hospitals in France, Canada, Italy, Greece, Belgium, and the Netherlands. We collected blood and adrenal samples from patients who had undergone unilateral or bilateral adrenalectomy for GIP-dependent primary bilateral macronodular adrenal hyperplasia with Cushing's syndrome. Adrenal samples from patients with primary bilateral macronodular adrenal hyperplasia who had undergone an adrenalectomy for overt or mild Cushing's syndrome without evidence of food-dependent cortisol production and those with GIP-dependent unilateral adrenocortical adenomas were used as control groups. We performed whole genome, whole exome, and targeted next generation sequencing, and copy number analyses of blood and adrenal DNA from patients with familial or sporadic disease. We performed RNA sequencing on adrenal samples and functional analyses of the identified genetic defect in the human adrenocortical cell line H295R. Findings: 17 patients with GIP-dependent primary bilateral macronodular adrenal hyperplasia with Cushing's syndrome were studied. The median age of patients was 43·3 (95% CI 38·8–47·8) years and most patients (15 [88%]) were women. We identified germline heterozygous pathogenic or most likely pathogenic variants in the KDM1A gene in all 17 patients. We also identified a recurrent deletion in the short p arm of chromosome 1 harboring the KDM1A locus in adrenal lesions of these patients. None of the 29 patients in the control groups had KDM1A germline or somatic alterations. Concomitant genetic inactivation of both KDM1A alleles resulted in loss of KDM1A expression in adrenal lesions. Global gene expression analysis showed GIP receptor upregulation with a log2 fold change of 7·99 (95% CI 7·34–8·66; p=4·4 × 10 −125 ), and differential regulation of several other G protein-coupled receptors in GIP-dependent primary bilateral macronodular hyperplasia samples compared with control samples. In vitro pharmacological inhibition and inactivation of KDM1A by CRISPR-Cas9 genome editing resulted in an increase of GIP receptor transcripts and protein in human adrenocortical H295R cells. Interpretation: We propose that GIP-dependent primary bilateral macronodular adrenal hyperplasia with Cushing's syndrome results from a two-hit inactivation of KDM1A, consistent with the tumour suppressor gene model of tumorigenesis. Genetic testing and counselling should be offered to these patients and their relatives. Funding: Agence Nationale de la Recherche, Fondation du Grand défi Pierre Lavoie, and the French National Cancer Institute.